Behaviour of electrical conductivity in CsI–Al2O3 and CsI–TiO2 systems - Saima Sultana; Rafiuddin (Arabian Journal of Chemistry, 2016)
This paper reports the effect of heterogeneously doped alumina and titania on the ionic conductivity of CsI. Composite materials (1 − x)CsI–xAl2O3 and (1 − x)CsI–xTiO2, x = 0–0.7 have been prepared and studied by X-ray diffraction (XRD), differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and impedance spectroscopy. The results confirmed the formation of a composite in which the interface layer plays an important role in controlling the bulk properties of the material. Enhancement of electrical conductivity is noticed with the increase in the mole percent (mol%) of dispersoid and the maximum enhancement is observed at x = 0.3 in case of alumina as well as titania. Arrhenius equation is used to study the effect of temperature on conductivity and activation energy. As the electrical conductivity increased, the activation energy was found to be decreased. The activation energy for CsI–xAl2O3 and CsI–xTiO2 systems was 0.713 and 0.677 eV, respectively.